Sugar Coated Formulations - Takan, Gokhan (2024)
The clustering of glycan ligands on the plasma membrane plays a crucial role in cell molecular recognition, as it enhances the selectivity and affinity of these ligands to specific receptors. Membrane lipids and proteins are distributed heterogeneously on the cell membrane, forming biophysically and biochemically distinct functional microdomains, such as lipid rafts. However, the spatial distribution of cell ligands and receptors within rafts and its effect on ligand binding and cellular recognition are not yet fully understood. This study has two primary objectives. Firstly, we aim to design ligands that can selectively sequester within liquid order and/or disordered phases within membranes. Secondly, we seek to investigate the effect of this phase sequestration on receptor binding. To achieve these goals, we have synthesized a library of mannose-MEAM polymers and galactose-containing control polymers with variable chain lengths via reversible-addition-fragment chain transfer (RAFT) polymerisation. We have then conjugated them to bis-azide containing cyanine membrane inserting dye by copper-catalysed azide-alkyne cycloaddition (CuAAC) click coupling. To analyse the phase partitioning behaviour of the resulting ligands, we have conducted experiments on synthetic Giant Unilamellar Vesicles (GUVs) and cell-derived Giant Plasma Membrane Vesicles (GPMVs). Receptor recognition potential of the ligands was also investigated on mannose receptor positive CHO cells. Through this study, we hope to gain a better understanding of how the spatial distribution of cell ligands and receptors within rafts affects ligand binding and cellular recognition.